2002
DOI: 10.1128/aem.68.11.5258-5264.2002
|View full text |Cite
|
Sign up to set email alerts
|

Postadaptational Resistance to Benzalkonium Chloride and Subsequent Physicochemical Modifications of Listeria monocytogenes

Abstract: Many studies have demonstrated that bacteria, including Listeria monocytogenes, are capable of adapting to disinfectants used in industrial settings after prolonged exposure to sublethal concentrations. However, the consequent alterations of the cell surface due to sanitizer adaptation of this pathogen are not fully understood. Two resistant and four sensitive L. monocytogenes strains from different sources were progressively subcultured with increasing sublethal concentrations of a surfactant, benzalkonium ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
125
0
13

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(145 citation statements)
references
References 32 publications
7
125
0
13
Order By: Relevance
“…The increase in saturated fatty acid (C 14:0 , C 16:0 , and C 18:0 ) and the decrease in unsaturated fatty acid (C 18:1 ) suggest that AR01/DGVS and DGRM2 were adapting to the presence of monolaurin by attempting to make the cell membrane more rigid and therefore potentially less permeable to monolaurin. Rigidification of the membrane has been suggested as a mechanism of resistance for membraneactive compounds such as nisin (34,38,55). It should be noted that when the cells were grown in the presence of monolaurin, lauric acid was incorporated into the cell membranes, resulting in changes in the fatty acid profile of the E. faecalis strains.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in saturated fatty acid (C 14:0 , C 16:0 , and C 18:0 ) and the decrease in unsaturated fatty acid (C 18:1 ) suggest that AR01/DGVS and DGRM2 were adapting to the presence of monolaurin by attempting to make the cell membrane more rigid and therefore potentially less permeable to monolaurin. Rigidification of the membrane has been suggested as a mechanism of resistance for membraneactive compounds such as nisin (34,38,55). It should be noted that when the cells were grown in the presence of monolaurin, lauric acid was incorporated into the cell membranes, resulting in changes in the fatty acid profile of the E. faecalis strains.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial cell surface hydrophobicity (CSH) was determined by the microbial adhesion to solvents (MATS) test based on affinity for nonpolar solvents (20). Xylene was used as the hydrocarbon phase.…”
mentioning
confidence: 99%
“…BC resistance has been detected in L. monocytogenes strains of different serotypes and from diverse sources (11)(12)(13)(14). Characterization of L. monocytogenes from foods and food processing plants revealed that most BC-resistant (BC r ) isolates were also resistant to the heavy metal cadmium, although the reverse was not always the case (14).…”
mentioning
confidence: 99%